Evaluation of the Stability of a 1,8-Cineole Nanoemulsion and Its Fumigant Toxicity Effect against the Pests Tetranychus urticae, Rhopalosiphum maidis and Bemisia tabaci - Rocío Ayllón-Gutiérrez; Eduardo Alberto López-Maldonado; Mariana Macías-Alonso; Joaquín González Marrero; Laura Díaz-Rubio; Iván Córdova-Guerrero (Insects, 2023)
Pest control is a main concern in agriculture. Indiscriminate application of synthetic pesticides has caused negative impacts leading to the rapid development of resistance in arthropod pests. Plant secondary metabolites have been proposed as a safer alternative to conventional pesticides. Monoterpenoids have reported bioactivities against important pests; however, due to their high volatility, low water solubility and chemical instability, the application of these compounds has been limited. Nanosystems represent a potential vehicle for the broad application of monoterpenoids. In this study, an 1,8-cineole nanoemulsion was prepared by the low energy method of phase inversion, characterization of droplet size distribution and polydispersity index (PDI) was carried out by dynamic light scattering and stability was evaluated by centrifugation and Turbiscan analysis. Fumigant bioactivity was evaluated against Tetranychus urticae, Rhopalosiphum maidis and Bemisia tabaci. A nanoemulsion with oil:surfactant:water ratio of 0.5:1:8.5 had a droplet size of 14.7 nm and PDI of 0.178. Formulation was stable after centrifugation and the Turbiscan analysis showed no particle migration and a delta backscattering of ±1%. Nanoemulsion exhibited around 50% more bioactivity as a fumigant on arthropods when compared to free monoterpenoid. These results suggest that nanoformulations can provide volatile compounds of protection against volatilization, improving their bioactivity.